1982
DOI: 10.1159/000182627
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Risk Factors in Patients Treated by Chronic Hemodialysis

Abstract: A survival analysis was applied to 1,453 patients treated between 1972 and 1978 in 33 French dialysis centers and prospectively followed up in the computerized Diaphane Dialysis Registry. 198 deaths (overall mortality = OM) were registered, of which 87 (43%) were secondary to cardiovascular complications (cardiovascular mortality = CVM). Risk factors for OM and CVM (p values < 0.05) were age, male sex, nephroangiosclerosis or diabetic nephropathy as the primary renal disease, elevated systolic and diastolic bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
235
2
14

Year Published

1983
1983
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 505 publications
(266 citation statements)
references
References 12 publications
15
235
2
14
Order By: Relevance
“…That there was no (23) found that low DBP was associated with a higher death rate and cardiovascular mortality. Degoulet et al (24) showed an association between both SBP and DBP and cardiovascular mortality in 1453 prospectively studied HD patients. Conversely, it was reported that no significant difference was found between the survival rates of 168 normotensive and 202 hypertensive patients (7).…”
Section: Discussionmentioning
confidence: 99%
“…That there was no (23) found that low DBP was associated with a higher death rate and cardiovascular mortality. Degoulet et al (24) showed an association between both SBP and DBP and cardiovascular mortality in 1453 prospectively studied HD patients. Conversely, it was reported that no significant difference was found between the survival rates of 168 normotensive and 202 hypertensive patients (7).…”
Section: Discussionmentioning
confidence: 99%
“…34,35 In contrast to trends seen in the general population, higher BMI has generally not been associated with an increase in mortality rate in patients receiving HD. [36][37][38][39][40][41] Johansen et al 40 reported that body fat and muscle mass, surrogates of body size, were both associated with improved survival in obese patients receiving HD, whereas Beddhu et al 42 showed that urinary creatinine level as a surrogate of muscle mass has a stronger association with survival than does body fat. 39,43 Only a very few studies have failed to confirm the survival advantages of obesity in patients with CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Several markers of malnutrition such as low body mass index and low serum albumin have been associated with high morbidity and mortality rates in this group of patients (3,4). Malnutrition in these patients is considered to be due to anorexia with low food intake (5)(6)(7), to the loss of nutrients and catabolism during the dialysis procedure (8,9), intercurrent illnesses (10), metabolic L.T.T.…”
Section: Introductionmentioning
confidence: 99%